The influence of smoking on the frequency and characteristics of complications following large loop excision of the transformation zone (LLETZ) - Vida Gavrić Lovrec; Tanja Erlah; Sarah Dobnik; Iztok Takač (Acta Medico-Biotechnica, 2021)
Purpose: Large loop excision of the transformation zone (LLETZ) is the procedure of choice for treating patients with suspected or confirmed cervical intraepithelial lesions. Since it has been established that smoking impairs wound healing, we wanted to determine if smoking increases the incidence of themost common complications that follow the LLETZ procedure and how it affects their intensity and duration.Methods: We included 434 patients that underwent the LLETZ procedure between 1993 and 2015 in the Department of Gynecology and Perinatology, University Medical Centre Maribor. Patients were asked to assess the intensity and duration of abdominal pain, vaginal bleeding and vaginal discharge after the procedure, and to complete a questionnaire on a daily basis. Data obtained from the questionnaires were then analysed.Results: The study group consisted of 237 (54.6%) smokers and 197 (45.4%) non-smokers. After the LLETZ procedure, 237 (54.6%) patients noted the occurrence of vaginal discharge, 193 (44.5%) lower abdominal pain, and 181 (41.7%) vaginal bleeding. No significant difference was observed in terms of the incidence of the observed events when comparing smokers and non-smokers. The duration and intensity of vaginal discharge and pain were not significantly different between the two groups. Non-smokers experienced bleeding that was more severe than smokers.Conclusions: According to the results of our study, smoking did not increase the incidence of vaginal bleeding, vaginal discharge, and lower abdominal pain following the LLETZ procedure, nor did it crucially influence their duration and intensity.